Laborchemische Schockraumdiagnostik beim pädiatrischen Polytrauma - Braun, C. K.; Weber, B.; Lackner, I.; Kalbitz, Miriam; Preßmar, J. (Pädiatrische Praxis, 2020)
Severe multiple trauma is the most common cause of death in children and presents a high socioeconomic burden. The most frequently injured organs are the head and the thorax, followed by injuries to the extremities as well as to the abdomen. The adequate assessment of the injuries is essential for the clinical course. X-ray and ultrasound besides thorough physical examination are crucial for the diagnosis. Additionally, for the exact evaluation of the injuries, chemical diagnostic parameters are evaluated. The examination of specific inflammatory markers such as interleukin-(IL)-6 and IL-8 have been shown to correlate with posttraumatic complications such as multiple organ failure. Further diagnostic parameters discussed are blood lactate values and the determination of parameters of plasmatic and cellular coagulation used to diagnose the acute trauma-associated coagulopathy. In order to determine severe injuries of the heart, liver and kidneys, specific organ damage markers could be analyzed in the patients' blood. The widely used routine organ-parameters like creatinine for the kidney and the liver-cell enzymes AST and ALT have shown to not be very practical for an evaluation of organ damage in the very early phase after multiple trauma. Troponin is a specific cardiac damage marker, which is systemically released from injured and damaged cardiomyocytes. The systemic release of troponin after polytrauma correlates with an increased mortality rate as well as with enhanced administration of catecholamines in adults and was also shown to be systemically released in multiple injured children, correlating with the severity of trauma and signs of organ failure. Summarized, the coincident use of imaging techniques and chemical diagnostic parameters for multiple injured children are indispensable for the evaluation of injuries at hospital admission as well as for the choice of the adequate therapy and prognosis.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Diagnostics; Emergency room; Outcome; Pediatric polytrauma